GAMBARAN SWITCHING COST DAN CUSTOMER SWITCHING BEHAVIOR PADA PELANGGAN MNC PLAY DI BANDUNG - Maelatusaadah, Lena Marliyana; Rahayu, Agus; Utama, Dian Herdiana (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - To find out the description of the level of switching cost and customer switching behavior in MNC Playâ€™s customer in Bandung. Design/methodology/approach - The design of this study is cross sectional method. This research uses descriptive approach with cross sectional method. A total of 106 respondents were selected using simple random sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is verification Â technique and descriptive technique.Findings - The result showed that switching cost is in good enough category, while customer switching behavior is in good enough category. Â Originality / value - The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study